2005
DOI: 10.4049/jimmunol.175.2.1301
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Positive Regulatory Domain I-Binding Factor 1 and X Box-Binding Protein 1 Transcription Factors by Multiple Myeloma-Reactive CTL

Abstract: Growing evidence indicates that multiple myeloma (MM) and other malignancies are susceptible to CTL-based immune interventions. We studied whether transcription factors inherently involved in the terminal differentiation of mature B lymphocytes into malignant and nonmalignant plasma cells provide MM-associated CTL epitopes. HLA-A*0201 (A2.1) transgenic mice were used to identify A2.1-presented peptide Ag derived from the plasma cell-associated transcriptional regulators, positive regulatory domain I-binding fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Lotz et al 39 suggested that the HLA-A2-restricted XBP1-specific human T cell repertoire is affected by partial self-tolerance. We examined whether the heteroclitic XBP1 peptides are able to break T-cell tolerance to this plasma cell-specific self-antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Lotz et al 39 suggested that the HLA-A2-restricted XBP1-specific human T cell repertoire is affected by partial self-tolerance. We examined whether the heteroclitic XBP1 peptides are able to break T-cell tolerance to this plasma cell-specific self-antigen.…”
Section: Discussionmentioning
confidence: 99%
“…This provides support that therapeutic approaches to trigger endogenous PRDM1 expression are feasible and could be a viable approach to induce apoptosis in lymphoma cells. Furthermore, PRDI-BF1 has been shown to be an important target in immunotherapy of myeloma by induction of PRDI-BF1-specific cytotoxic T cells, an approach which could also be exploited to kill lymphomas after PRDI-BF1 induction (41). …”
Section: Discussionmentioning
confidence: 99%
“…Blimp‐1 was chosen as a third target (and second self‐antigen) in our attempt to triangulate CTL responses against plasma cells primarily because of its upregulation in that lymphocyte subset and its critical role in plasma cell development and thereby in AL amyloidosis pathogenesis. The prediction that CTL generated with Blimp‐1‐derived peptide(s) would be clinically effective is supported by the ability of CTL generated in mice with HLA‐A2‐binding human Blimp‐1‐derived peptides, including one peptide that shares the T‐cell‐binding domain with our murine Blimp‐1 470−478 (FPRL), to lyse HLA‐A2 + human myeloma cell lines and primary plasma cells 54 . Although the human Blimp‐1 peptides in Lotz et al 54 were not self‐antigens in the HLA‐transgenic mice, these results demonstrate that Blimp‐1 peptides are processed and presented by malignant human plasma cells such that they can be recognized by peptide‐induced CTL.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction that CTL generated with Blimp‐1‐derived peptide(s) would be clinically effective is supported by the ability of CTL generated in mice with HLA‐A2‐binding human Blimp‐1‐derived peptides, including one peptide that shares the T‐cell‐binding domain with our murine Blimp‐1 470−478 (FPRL), to lyse HLA‐A2 + human myeloma cell lines and primary plasma cells 54 . Although the human Blimp‐1 peptides in Lotz et al 54 were not self‐antigens in the HLA‐transgenic mice, these results demonstrate that Blimp‐1 peptides are processed and presented by malignant human plasma cells such that they can be recognized by peptide‐induced CTL. Importantly, this conclusion is supported by our studies in which modest but statistically significant decreases in plasma cell percentages were observed in the spleens, lymph nodes and bone marrow of mBlimp‐1 470−478 ‐immunized mice and a significant decrease in absolute number of splenic plasma cells was documented (Figure 6).…”
Section: Discussionmentioning
confidence: 99%